EXPRESSION OF CYCLIN D1 IN VARYING GRADES OF ORAL SQUAMOUS CELL CARCINOMA: AN IMMUNOHISTOCHEMICAL STUDY - ANJUM, RUBEENA; Hussain, Mohd; KAUR, MANDEEP; KHAJURIA, NIDHI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Cyclin D1 promotes cell cycle progression during G1 phase, a key event in G1-S transition. It is a positive regulator of cell cycle. Overexpression may lead to disturbance in normal cell cycle control and tumor formation. The objective of the study was to evaluate the expression of cyclin D1 in varying grades of oral squamous cell carcinoma (OSCC). Methods: Nine formalin-fixed paraffin embedded tissues were immunohistochemically analyzed for the expression of cyclin D1 in varying grades of OSCC. Results: Expression of cyclin D1 was more in poorly differentiated OSCC than moderately and well-differentiated OSCC. Conclusion: Increased expression of cyclin D1 was seen in poorly differentiated OSCC and thus can be used as a biomarker for the aggressiveness of OSCC.